Answer:
I'll say x = 8
Explanation:
because Simplifying
2x + -3 = 3x + -11
Reorder the terms:
-3 + 2x = 3x + -11
Reorder the terms:
-3 + 2x = -11 + 3x
Solving
-3 + 2x = -11 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
-3 + 2x + -3x = -11 + 3x + -3x
Combine like terms: 2x + -3x = -1x
-3 + -1x = -11 + 3x + -3x
Combine like terms: 3x + -3x = 0
-3 + -1x = -11 + 0
-3 + -1x = -11
Add '3' to each side of the equation.
-3 + 3 + -1x = -11 + 3
Combine like terms: -3 + 3 = 0
0 + -1x = -11 + 3
-1x = -11 + 3
Combine like terms: -11 + 3 = -8
-1x = -8
Divide each side by '-1'.
x = 8